2021
DOI: 10.51910/ijhdr.v17i3-4.949
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of Zincum metallicum in maternal deprivation-induced behavioral disturbances in female rats

Abstract: Background: Clinical studies have shown that adverse events in early life are quite stressful and can lead to the development of psychiatric disorders, such as anxiety, in adolescence and adulthood in humans. Experimental models of maternal deprivation (MD) in rats can be a useful tool for the understanding how these events in the early period of development can lead to behavioral changes in adulthood. Aims: The objective of this study was to evaluate the long-term effects of Zincum metallicum (Zinc met) homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…The study concluded that additional research is still required to comprehend the physio-pathological underpinnings of these effects. 21 Another study looked at the effects of sodium arsenate on the behaviour of zebrafish (Danio rerio) by analysing the locomotor activity and anxiety-related parameters to see if the ultra-diluted substances can reduce the neurobehavioral effects or not. Arsenicum album proved to be more effective as a potential anxiolytic by reversing the anxiety of the animals that were intoxicated with heavy metal sodium arsenate in a 6cH dilution.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that additional research is still required to comprehend the physio-pathological underpinnings of these effects. 21 Another study looked at the effects of sodium arsenate on the behaviour of zebrafish (Danio rerio) by analysing the locomotor activity and anxiety-related parameters to see if the ultra-diluted substances can reduce the neurobehavioral effects or not. Arsenicum album proved to be more effective as a potential anxiolytic by reversing the anxiety of the animals that were intoxicated with heavy metal sodium arsenate in a 6cH dilution.…”
Section: Discussionmentioning
confidence: 99%